Pengaruh Promosi Jabatan dan Pengawasan Terhadap Kepuasan Kerja Karyawan Pada PT. Berliando Mitra Abadi di Denpasar - Ni Kadek Widiantari; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aims to tell whether promotion has an influence on employees’ job satisfaction at PT. Berliando Mitra Abadi in Denpasar. Causal research is used in this study that has characteristics related to cause and effect. In this study the population used was 62 (sixty-two) employees of PT. Berliando Mitra Abadi in Denpasar. In the sampling technique using saturated samples by conducting non probability sampling. So that the determination of the sample is 62 (sixty-two) respondents. How to collect data through a questionnaire survey method is carried out by distributing questions to the respondents. Then the data were analyzed multiple linier regression, t test and F test. The study shows an indication that there is a partial and simultaneous of employee job satisfaction at PT. Berliando Mitra Abadi in Denpasar.